Behind The Scenes: The Vital Role Of Dental Assistants In Oral Healthcare (Journal of Namibian Studies : History Politics Culture, 2023)
This article delves into the indispensable role of dental assistants in providing comprehensive oral healthcare. While often working behind the scenes, dental assistants play a crucial part in ensuring the smooth operation of dental practices and the delivery of high-quality patient care. This article explores the diverse responsibilities of dental assistants, including patient preparation, chair-side assistance, sterilization procedures, and administrative tasks. Additionally, it highlights the importance of effective communication and teamwork between dental assistants, dentists, and other members of the dental team. By shedding light on the essential contributions of dental assistants, this article aims to enhance appreciation for their vital role in promoting oral health and well-being.